Evaluation of the Immune Response Against Immature Viral Particles of Infectious Pancreatic Necrosis Virus (Ipnv): A New Model to Develop an Attenuated Vaccine - Spencer-Ossa, E; Sandino-Garcia, A; Imarai-Bahamonde, C; Rivas-Aravena, A; Cortez-San Martin, M (2012)
Infectious pancreatic necrosis virus (IPNV) is a worldwide problem affecting both freshwater and seawater fish. Vaccines developed against IPNV are not as efficient in the field as they are in tests. Moreover, research in the development of vaccines against IPNV has often shown that vaccines can stimulate the immune response of fish antibodies but do not protect efficiently against IPNV. In fact, sometimes dead infected fish show high antibody titers against IPNV. This suggests that the magnitude of total antibodies stimulated by the vaccine is not necessarily related to the level of protection against IPN, suggesting that a new method is needed to evaluate vaccine stimulation of the immune system. We propose in vitro evaluation of the non-specific cytotoxic cells (NCC) of the innate immune response, in addition to humoral specific response. Moreover, it is necessary to develop innovative methods to improve fish vaccines. In this work, IPNV replicative intermediaries (provirus) were used to inject rainbow trout fry, which is the most vulnerable state to IPNV. To evaluate the immune response triggered by this vaccine, NCC and total and neutralizing antibodies against IPNV and the provirus were determined. Results indicated that NCC activity in rainbow trout fry is triggered by IPNV infection. Both IPNV and the provirus stimulate humoral and NCC immune response in rainbow trout fry. Although the total antibodies triggered by the provirus were half of that triggered by IPNV infection, the number of neutralizing antibodies was similar in the two treatments. This suggests that the ratio of neutralizing antibodies is higher among the antibodies stimulated by provirons than among those stimulated by IPNV infection. Thus, immature provirus is sufficient to activate immune response and is a good candidate as an attenuated vaccine in rainbow trout fry. In addition, neutralizing antibodies, together with non-specific cytotoxic activity, are a more suitable strategy to evaluate new vaccines than humoral immune response alone. © 2012.